Morphological phylogenetic analysis of genus Xanthopimpla Saussure 1892 (Hymenoptera: Ichneumonidae: Pimplinae) from Malaysia - David, A.D.; Idris Abd. Ghani, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
A phylogenetic analysis based on morphological data was done for 31 species of Xanthopimpla Saussure 1892 (Hymenoptera: Ichneumonidae: Pimplinae) from Malaysia by using PAUP*4.0. A total of 83 characters were analysed using Maximum Parsimony heuristic search with 100 replications and 2 outgroups namely Theronia pseudozebra pseudozebra Gupta 1962 and Echthromorpha agrestorius notulatoria Fabricius 1804. Resulted tree are less resolved and supported with length of tree value 351, Consistency index 0.3105, Retention index 0.4622, Rescale Consistency index 0.1435 and Homoplasy index 0.6895. Outcome forms monophyletic branches amongst ingroups. Xanthopimpla leviuscula deviated out from the clade due to the absence of notaulus with 62% bootstrap value. Conflict arose when resulted cladogram compared with group-classification by Townes & Chiu (1970). To simplify, X. melanacantha melanacantha + X. corynoceros corynoceros clade approves classifications into Rhopaloceros-group by Townes & Chiu (1970) by 57%. However, cladogram opposes classification of X. decurtata detruncata, X. polyspila and X. flaviceps into Terebatrix-groups as they did not belong to the same clade. Therefore, further phylogenetic studies should be conducted by using molecular data to form more reliable phylogenetic tree.